2014
DOI: 10.1063/1.4855056
|View full text |Cite
|
Sign up to set email alerts
|

Structural, vibrational, and quasiparticle band structure of 1,1-diamino-2,2-dinitroethelene from ab initio calculations

Abstract: The effect of pressure on the structural and vibrational properties of the layered molecular crystal 1,1-diamino-2,2-dinitroethelene (FOX-7) are explored by first principles calculations. We observe significant changes in the calculated structural properties with different corrections for treating van der Waals interactions to Density Functional Theory (DFT), as compared with standard DFT functionals. In particular, the calculated ground state lattice parameters, volume and bulk modulus obtained with Grimme's … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 60 publications
(81 reference statements)
5
27
0
Order By: Relevance
“…There have been promising attempts made to fix this shortcoming, and considerable benchmarking studies are available with advanced methods for noble gas solids, layered, sparse and molecular crystals. [22][23][24][25][26][27][28][29][30][31][32] In the case of energetic materials, Sorescu et al 33 35 From our previous studies on nitromethane and FOX-7 solids, 36,37 we also found good agreement using Grimme and TS methods. However, it is observed that although the mentioned dispersion corrected methods overcomes most of the difficulty in reproducing ground state volumes, the relative errors still show a mean absolute deviation of about 3 %.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…There have been promising attempts made to fix this shortcoming, and considerable benchmarking studies are available with advanced methods for noble gas solids, layered, sparse and molecular crystals. [22][23][24][25][26][27][28][29][30][31][32] In the case of energetic materials, Sorescu et al 33 35 From our previous studies on nitromethane and FOX-7 solids, 36,37 we also found good agreement using Grimme and TS methods. However, it is observed that although the mentioned dispersion corrected methods overcomes most of the difficulty in reproducing ground state volumes, the relative errors still show a mean absolute deviation of about 3 %.…”
Section: Introductionsupporting
confidence: 59%
“…43,44 But the well known disagreement of the computed band gap using standard DFT functionals leads to an inaccurate estimation of the properties related to the band gap either in molecular or solid systems. However from our previous studies on some energetic materials (solid nitromethane, FOX-7, cynauric triazide) 36,37,45 and another theoretical study on TATB by Fedorov et al, 46 it is known that the GW approximation [47][48][49][50][51][52] can overcome this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the presence of hydrogen bonding, it can be expected that the N-H strengthening frequency decreases (red-shift) with increasing pressure and this red-shift leads to strengthening of hydrogen bonding. 28 In addition, our previous 37,38 studies on hydrogen bonded systems, and those of Pravica et al, 39 suggest that the red-/blue-shift in the mid-IR frequencies stabilizes/destabilizes the system under high pressure. Therefore, in the present study, we have also calculated the IR spectra under pressure up to 30 GPa to get spectroscopic picture of the hydrogen bonding for the TMAA and HZA compounds under hydrostatic compression.…”
Section: Ir Spectra Under Pressurementioning
confidence: 87%
“…Although its low sensitivity to impact and shock waves is of considerable interest, the microscopic factors governing this behavior are not well understood. To gain insight into this behavior several experimental [6][7][8][9][10] and theoretical [11][12][13][14][15] studies have been conducted to characterize the molecular response of FOX-7 at high pressures. In accord with its low sensitivity to initiation, it was recently shown that FOX-7 single crystals are chemically stable over a broad range of pressure [10].…”
Section: Introductionmentioning
confidence: 99%